Who 'framed' Ramchandra Siras? Journalistic discourses of sexual citizenship in India. (September 2020) - Ejaz, Khadija; Moscowitz, Leigh
In 2010, a professor in India was forcibly outed as gay and catapulted into a nationwide debate about LGBTQ rights in India. A textual analysis of prominent Indian English-language newspapers revealed the framing devices journalists used to report the case, unpacking how coverage essentialized gay identity, signified civil rights and citizenship, problematized notions of consent, complicated public/private demarcations of sexuality, and negotiated competing claims of morality. Journalistic discourse inevitably privileged dominant western neoliberal conceptions of sexuality, reducing sexual citizenship to a particular classed and gendered subject at the expense of a more expansive range of alternative sexualities in India.